A 'placeful' station? The community role in place making and improving hedonic value at local railway stations. (December 2015) - Alexander, Matthew; Hamilton, Kathy
Highlights: We explore the local community role in regenerating railway stations. Community appropriation of stations leads to an increased sense of ownership. Through community involvement a sense of place is engendered and developed. Station adoption results in place transformation and feelings of placefullness. Abstract: In recent years, railway stations have come to be seen as non-places within society, points of transit and nothing more. The role of the station in place making is disputed with stations seen as both creating and destroying a sense of place within a community. Our study is located within the railway stations of Scotland and explores how local communities have been empowered to reclaim, customise, and re-appropriate stations to simultaneously create a sense of place and better promote their community to the outside world. Drawing on ethnographic research we refute the notion that stations are somehow 'placeless'. We show how through a process of legitimisation, a sense of ownership and appropriation of the station environment, communities are able to transform the station, improving hedonic value and recapturing a sense of place.